Research on wireless coverage area detection technology for 5G mobile communication networks - Hongjun Wang; Yu Zhou; Wenhao Sha (International Journal of Distributed Sensor Networks)
In the field of 5G mobile communication networks, coverage performance is an important indicator that can affect the user’s terminal experience. The current method for coverage detection is drive test, which is based on mobile terminals. Although the application of the technology in practice has matured, the implementation of drive test requires additional time and manpower. However, in the test phase of a 5G mobile communication network, the detection should be on-the-spot, real time, and repeatable. To overcome these challenges, this article proposes 5G network wireless coverage area detection technology that is based on wireless sensor networks. First, sensor nodes are deployed to collect the received signal strength. Second, the algorithm performs Gaussian filtering on collected data. Then, an interpolation estimation algorithm is adopted to estimate the interpolation of the area. Finally, the data collected by sensor nodes and estimated by interpolation points are integrated to generate the effective coverage area status. To overcome the human subjectivity of the traditional model fitting when performing the variation function fitting in the interpolation estimation, a support vector regression algorithm is employed. The simulation results indicate that the algorithm can rapidly and correctly detect the coverage area of a 5G mobile communication network.